Frost Action in Soils Fundamentals and Mitigation in a Changing Climate - Shoop, Sally A. (American Society of Civil Engineers, 2020)
Prepared by the Frozen Ground Committee and the Transportation and Infrastructure Committee of the Cold Regions Engineering Division of ASCEFrost Action in Soils: Fundamentals and Mitigation in a Changing Climate presents the challenges of cold regions engineering in a changing climate, as well as the current practices and state-of-the-art tools for addressing them. Climate change poses questions regarding associated effects on freeze-thaw action and the potential impacts on pavements and other structures in cold regions. In the last 35 years, significant technological advancements addressing frost action in soils have occurred; and tools for instrumentation, measurement, and computer analysis have improved considerably. Thebook explores frost action in soils from different perspectives, as presented in three parts. The first section presents the fundamentals of frost heave and thaw weakening, the impacts on roads and other structures, and the projected effects of climate change on frost action. The second section presents mitigation of frost heave and thaw weakening within pavement structures. The third section highlights three case studies dealing with frost action and mitigation for buildings, roadways, and airfields. This book is a valuable resource for engineers, scientists, and government agencies involved in cold regions engineering and the mitigation of frost action on pavements and other structures.
Keywords: Frost heaving.; Frozen ground.; Soil freezing.; elektronické knihy; electronic books